On Reyes Mate’s Theory of the Victim: Metaethical Sketches on Injustice - Gan-Krzywoszyńska, Katarzyna; Leśniewski, Piotr (ETHICS IN PROGRESS, 2013)
The aim of our paper is twofold. Firstly, very original approach to the question of victims elaborated very thoroughly by Reyes Mate is presented. Unfortunately, his conceptualization of victimology is relatively little known outside Spanish and Latin American culture. It is meant as a basis for adequate theory of injustice and justice. Secondly, comprehensive and detailed metaethical analyses of fundamental concepts used by Reyes Mate are developed here by means of standard methods, i.e. triangle, hexagon, and octagon of logical oppositions.